Acute hemolytic reaction by anti-Wra: Case report and review of the hemovigilance database of a tertiary care hospital. (June 2022) - Solves, Pilar; Tur, Susana; Gómez-Seguí, Inés; Viel, María; Eiris, Juan; Planells, Yolanda; Rodríguez, Raquel; Peñalver, Isabel; Castro, Emma; de la Rubia, Javier
Abstract: Wra is the most common LIA in white population. The incidence of Wra antigen in Spanish population has been estimated to be 1 in 785 in blood donors, while anti-Wra was found in 2.7 % and 3.6 % of healthy donors and transfused patients respectively. Severe, even fatal hemolytic transfusion reactions and hemolytic disease of the newborn caused by anti-Wra have been reported. Since the reagent red blood cells used for antibody screening usually lack Wra antigen, the anti-Wra is not detected and hemolytic reaction could occur if transfusion is performed by type and screen approach. We report an acute hemolytic reaction due to anti-Wra in a patient with negative antibody screening. We have also reviewed the records of the hospital hemovigilance database in order to collect the previous hemolytic cases due to anti-Wra. During a 21-year period 461, 539 red blood cell units have been transfused to 81, 614 patients in our hospital. Alloimmnunization was detected in 3840 patients (0.83 %) and anti-Wra was detected in 22 patients (1/3709), 10 of whom had other alloantibodies, and only in 1 occasion (this case) has been implicated in mild hemolytic acute transfusion reaction. In our experience, the risk of fatal hemolytic reaction due to LIA in hospitals with blood services using the type and screen policy is extremely low.